Building Economic Independence for Indonesian Immigrants in Malaysia Through Improved Financial Literacy - Yanto, Heri; Baroroh, Niswah; Pertiwi, Meilani Intan; Airyq, Irnin Miladdyan (Unram Journal of Community Service, 2025)
Indonesian migrants in Malaysia face significant economic vulnerability due to low and unstable incomes, limited access to formal financial services, and insufficient financial literacy. These conditions often lead to poor money management, debt dependency, and lack of long-term financial planning. This community service program aimed to enhance the financial literacy of Indonesian migrants in Malaysia as a strategy to strengthen their economic independence. Using the Participatory Action Research (PAR) method, the program involved migrants as active partners in identifying financial challenges, designing relevant training, and implementing practical solutions. Activities included daily financial management workshops, budgeting simulations, and introductions to simple financial applications. Conducted in Kuala Lumpur over eight months, the program reached participants from various informal sectors. The results showed increased participants’ ability to record expenses, plan budgets, set savings goals, and encourage productive financial practices within their families. The initiative also fostered awareness of the benefits of formal financial services. In conclusion, improving financial literacy through a participatory approach can serve as an effective catalyst for empowering migrants to achieve sustainable economic independence.